Understanding empathy and theory of mind in Romanian dental students for improved educational strategies - Ancuta Mioara Banu; Sorin Ursoniu; Smaranda Laura Gotia; Salomeia Putnoky; Costela Lacrimioara Serban (Scientific Reports)
Abstract Empathy and theory of mind (ToM) are critical components of social cognition that significantly impact patient care. This study evaluates the levels of empathy and ToM among dental students in Romania, examining demographic influences and predictors of high empathy. Utilizing the Toronto Empathy Questionnaire, the Reading the Mind in the Eyes Test and sociodemographic questions, the study involved 300 dental students, 78.3% females, with a median age of 22. Statistical analyses included the chi-square, Mann–Whitney and correlation tests. Logistic regression was used for the prediction of the highest tertile of empathy. The findings revealed that 73.3% of students had higher-than-average levels of empathy. High empathy is associated in a multivariate model with female gender (OR 2.032, 95% CI 1.041–3.963), excellent or very good perceived health status (OR 1.903, 95% CI 1.143–3.167), and theory of mind (OR 1.078, 95% CI 1.011–1.149). However, the year of study and perceived stress levels did not significantly influence empathy scores. A subset of students (25.6%) showing below-average ToM scores raises concerns, emphasizing the need for further investigation and screening of possible related conditions to enable early detection and intervention. These findings underscore the importance of incorporating empathy training and cognitive skill development into dental education to foster patient-centered care and address the emotional and cognitive needs of future practitioners.